Elucidating the function of mycorrhizal-induced Kunitz protease inhibitors and characterization of their putative target proteases in Medicago truncatula - Hirsch, Stefanie S. (KIT Scientific Publishing, 2014)
Most terrestrial plants live in symbiosis with arbuscular mycorrhizal fungi. In this study, a mycorrhizal-induced gene family of Medicago truncatula encoding putative Kunitz protease inhibitors was functionally characterized by means of biomolecular, biochemical, microscopical and in silico methods. Their putative target proteases were identified among a clan of serine carboxypeptidases. Results suggest that both protein families work functionally together to control mycorrhizal establishment.